The MQRG score: a novel prognostic tool for adrenocortical carcinoma patients based on mitochondrial quality - Chen, Tao; Wang, Yifan; Chen, Xue; Zheng, Wenbin; Guo, Weiquan; Liang, Qi; Wang, Jing; Chen, Zhongbiao; Zhou, Yiwen; Xiao, Lijia (Frontiers in Endocrinology, 2024)
Mitochondrial quality plays a pivotal role in preserving normal cellular functions. Our observations of aberrant expression of proteins associated with mitochondrial metabolism in adrenocortical carcinoma (ACC) patients suggest a plausible connection between mitochondrial quality and ACC development. Nevertheless, a comprehensive comprehension of this relationship at the molecular and genetic levels necessitates further exploration. In this study, we delved into the distinctions among Mitochondrial Quality-Related Genes (MQRGs) concerning Overall Survival (OS) and Disease-Free Survival (DFS) in different ACC subtypes. Furthermore, we introduced a novel MQRG scoring system designed to guide clinical prognosis and predict immune therapy response. Our findings reveal that, in ACC samples, the majority of MQRGs exhibit upregulated expression, correlating with an unfavorable prognosis. Validation establishes the MQRG score as an independent prognostic factor for ACC, with the high-risk MQRG score group demonstrating significantly abbreviated overall survival. Through the scrutiny of MQRGs, we gain a more profound understanding of potential variances in the tumor microenvironment of ACC patients, offering insights for clinical decision-making and prognosis forecasting.